Relation between aphasia and arcuate fasciculus in chronic stroke patients - Tak, Hyung Jun (BioMed Central, 2014)
BACKGROUND: The role of the arcuate fasciculus (AF) in the dominant hemisphere in stroke patients with aphasia has not been clearly elucidated. We investigated the relation between language function and diffusion tensor tractography (DTT) findings for the left AF in chronic stroke patients with aphasia. METHOD: Twenty five consecutive right-handed stroke patients with aphasia following lesions in the left hemisphere were recruited for this study. The aphasia quotient (AQ) of Korean-Western Aphasia Battery was used for assessment of language function. We measured values of fractional anisotropy (FA), apparent diffusion coefficient (ADC), voxel number of the left AF. We classified patients into three groups: type A - the left AF was not reconstructed, type B - the left AF was discontinued between Wernicke’s and Broca’s areas, and type C – the left AF was preserved around the stroke lesion. RESULTS: Moderate positive correlation was observed between AQ and voxel number of the left AF (r = 0.471, p < 0.05). However, no correlation was observed between AQ and FA (r = 0.275, p > 0.05) and ADC values (r = -0.286, p > 0.05). Significant differences in AQ scores were observed between the three types (p < 0.05); the AQ score of type C was higher than those of type A and B, and that of type B was also higher than that of type A (p < 0.05). CONCLUSION: According to our findings, the remaining volume of the left AF, irrespective of directionality and diffusivity, showed moderate positive correlation with language function in chronic stroke patients with aphasia. Discontinuation or non-construction of the left AF was also an important factor for language function.